Responses of endothelial cells, smooth muscle cells, and platelets dependent on the surface topography of polytetrafluoroethylene. Issue 9 (17th May 2016) - Lamichhane, Sujan; Anderson, Jordan A.; Remund, Tyler; Sun, Hongli; Larson, Mark K.; Kelly, Patrick; Mani, Gopinath
Abstract: In this study, the effect of different structures (flat, expanded, and electrospun) of polytetrafluoroethylene (PTFE) on the interactions of endothelial cells (ECs), smooth muscle cells (SMCs), and platelets was investigated. In addition, the mechanisms that govern the interactions between ECs, SMCs, and platelets with different structures of PTFE were discussed. The surface characterizations showed that the different structures of PTFE have the same surface chemistry, similar surface wettability and zeta potential, but uniquely different surface topography. The viability, proliferation, morphology, and phenotype of ECs and SMCs interacted with different structures of PTFE were investigated. Expanded PTFE (ePTFE) provided a relatively better surface for the growth of ECs. In case of SMC interactions, although all the different structures of PTFE inhibited SMC growth, a maximum inhibitory effect was observed for ePTFE. In case of platelet interactions, the electrospun PTFE provided a better surface for preventing the adhesion and activation of platelets. Thus, this study demonstrated that the responses of ECs, SMCs, and platelets strongly dependent on the surface topography of the PTFE. © 2016 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 104A: 2291–2304, 2016.